Investigation of adsorption of isoniazid derivatives at mild steel/hydrochloric acid interface: Electrochemical and weight loss methods - Singh A.K.; Quraishi M.A. (My University, 2025)
The corrosion inhibition properties of isoniazid derivatives, namely N-(morpholino methyl) isatin-3-isonicotinoyl hydrazone (MIIH), N-(piperazino methyl) isatin-3-isonicotinoyl hydrazone (PIIH), N-(2-Thio benzimidazolyl methyl) isatin-3-isonicotinoyl hydrazone (TBIH), N-(piperadino methyl) isatin-3-isonicotinoyl hydrazone (PIIIH) for mild steel corrosion in 1 M HCl medium were analysed by electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and weight loss techniques. Electrochemical impedance data demonstrated that the addition of the isoniazid derivatives in the corrosive solution decreased the charge capacitance and simultaneously increased the function of the charge/discharge of the interface, facilitating the formation of an adsorbed layer over the steel surface. Adsorption of these inhibitors on the steel surface obeyed the Langmuir adsorption isotherm. Potentiodynamic polarization studies showed that all the tested inhibitors affected both the anodic and cathodic process, thus they can be classified as mixed type of inhibitor. The effect of chemical structure of the four tested inhibitors was discussed. It was found that the efficiency order followed by molecules tested was TBIH > PIIH > MIIH > PIIIH. Thus TBIH turned out to be the best inhibitor. This fact strongly suggests that, an efficient corrosion inhibitor molecule should be large one, planar, having unoccupied d-orbital and also containing an extensive number of π-electrons. © 2010 Elsevier B.V. All rights reserved.